Effects of the Sustainable Forestry Initiative on Landscape Pattern and Processes - Azevedo, João (2006)
We used simulation modeling to study the changes in landscape pattern and function resulting from the application of the Sustainable Forestry Initiative (SFI) program in East Texas, USA. Changes in landscape structure were examined by comparing landscapes with different management histories. The effects of pattern on processes were analyzed considering vertebrate habitat quality and configuration and hydrological processes such as water and sediment yield. Landscapes managed according to the SFI program presented increased general fragmentation. The application of measures under SFI increased habitat diversity in the landscape as well as Habitat Suitability Index (HSI) values for most of the species. Habitat for species requiring large patches of mature forest was almost absent. Landscapes managed under the SFI program showed lower sediment yield at the watershed level than those under the non-SFI program due to higher channel erosion related to the absence of buffer strips in the non-SFI scenario.